Ideologia hip-hopowa na przykładzie tekstów hip-hopowych - Kozłowska, Monika (Kultura-Społeczeństwo-Edukacja, 2012)
The article is asort of analysis of hip hop lyrics in the context of their importance for identity formation process of young generation. Rap music, as one of the elements of hip hop culture, is a kind of special innovation for its audience. With rising interest for this musical genre and hip hop culture the discussion on formulating the issues through the prism of rap music’s message has been increasing. The article presents certain aspects of making sense to the reality, which surrounds young artists, as well as some attempts at interpretation of already formulated social messages and their content. On one hand, the content is presented as a piece of announcement or message, which expresses young generation identity through the music. On the other hand, the content is a kind of confrontation between young audience and various messages presented in particular piece of music. In the article various hip hop productions are analyzed. The analysis is based on objective attitude towards the problem and presents both positive and negative sides of the issue, which have an in uence on identity formation process of teenagers.